Paradigmkrig och fred: om argumentationsanalysen som integrerande grund inom socialvetenskap (Sociologisk Forskning, 1995)
Paradigm war and peace: argumentation analysis as a basis for integrationThis article shows that argumentation theory can serve as a fruitful methodological basis for empirical research in social science. Choosing this methodological perspective makes it possible to integrate criticism and methods, deriving from opposing positions in the so called paradigm wars, into a rational discourse. This is illustrated by means of an example of social work research concerning traumatic experiences and distinct phases in the process of recovery.